Effect of postharvest dips on apple surface microflora and Dasineura mali removal - Scheper, R.W.A.; Rogers, D.J. (New Zealand Plant Protection, 2008)
The effectiveness of six prewashing and nine postwashing dips on loosening apple leaf curling midge (ALCM) cocoons and reducing fruit surface microflora respectively was examined In the laboratory fungal populations were significantly reduced (1217 cfu/cm2) after 10min dips in medium or high concentration Nylate (5 ppm or 10 ppm free Cl2) or SteriMaxTM (008) compared with controls (5367 cfu/cm2) An ethanol dip (1 min 50) significantly reduced fungal and yeast populations compared with all other treatments Dips in low concentration controlledrelease chlorine products (10 min) and in sodium hypochlorite (1 min 100 ppm free Cl2) did not affect fungal populations significantly The same products except ethanol which was replaced by an antifoam solution (075) were tested on ALCM cocoons but none loosened cocoons effectively compared with the control In a packhouse a 6min postwashing dip in high concentration Nylate (75 ppm free Cl2) significantly reduced fungal (25 cfu/cm2) and yeast (12 103 cfu/cm2) populations compared with washed and unwashed apples (274 fungal cfu/cm2 and 23 104 yeast cfu/cm2) Both laboratory and packhouse studies indicated that postwashing dips can lower the apple surface microflora which may reduce storage rot incidence However the prewashing dips did not appear to loosen ALCM cocoons